Approximation by rational functions in Morrey-Smirnov classes - Ali, Mohammad; Mahmoud, Suliman; kinj, Ahmed (Kuwait Journal of Science, 2018)
In this article, we investigate the direct problem of approximation theory in Morrey-Smirnov classes of analytic functions, defined on a doubly-connected domain bounded by two sufficiently smooth curves.